Violent conflict and expectation about the economy's performance: Evidence from Nigeria - Daniel Tuki (Economics Letters, 2024)
This study examines how exposure to violent conflict influences individuals' expectations about Nigeria's future economic performance. It employs forest cover as an instrumental variable to identify the causal effect of violent conflict on expected economic performance. The regression results reveal that violent conflict makes people pessimistic about the economy's future performance. This might be because conflict disrupts socioeconomic activities and causes psychological distress, making people less hopeful about the future.
Keywords: D01; D74; O40; E66; 330; Violent conflict; Terrorism; Expectation; Economy; Kaduna State; Nigeria